IMPLEMENTASI PEER TEACHING SANTRI ALIYAH DALAM PEMBELAJARAN NAHWU-SHARAF PADA SANTRI TSANAWIYAH DI PESANTREN BABUSSALAM ACEH SINGKIL - Yunita Sari; Salami Mahmud; Nurbayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of the peer teaching method in the learning of nahwu and sharaf at Pesantren Babussalam Aceh Singkil as an effort to strengthen students’ understanding of classical Islamic texts (kitab kuning) through a collaborative learning approach. The study is grounded in the need of Islamic boarding schools to develop adaptive, effective, and contextual learning strategies amid the challenges of globalization and varied student abilities. Using a qualitative descriptive approach, the unit of analysis includes aliyah students as tutors, tsanawiyah students as learners, and teachers and boarding supervisors as supporting informants. Data were collected through observation, interviews, and documentation, and analyzed interactively through data reduction, presentation, and conclusion drawing. The findings reveal that the application of peer teaching enhances students’ linguistic comprehension, fosters learning independence, and strengthens social solidarity across levels. Moreover, it cultivates religious character and social responsibility among senior students as part of internalizing Islamic leadership values. The study implies that pesantren-based learning innovations can serve as an alternative model for strengthening Islamic Education learning practices.